Effects of fat level and calorie-protein ratio on performance of finishing pigs - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty finishing pigs averaging 52.9 kg (116 lbs.) initially were used to study effects of fat level and calorie-protein (C:P) ratio on performance and carcass traits of pigs fed a sorghum-soybean meal basal ration. The basal ration contained 13.1% crude protein, 0.55% lysine, 0.68% calcium and 0.59% phosphorus. Fat (tallow) was added to the basal ration at the expense of sorghum at 0, 3, 6, and 9% while maintaining a constant C:P ratio. Also, 9% fat was added to the basal ration without adjusting the C:P ratio. With a constant C:P ratio, daily gain and feed efficiency were improved by adding fat. Pigs fed the basal ration supplemented with 9% added fat while maintaining a constant C:P ratio gained faster and were more efficient (P<.05) than pigs fed 9% added fat without adjusting the C:P ratio. Carcass data were collected on 75 pigs at approximately 100 kg (220 lbs.). Adding fat resulted in a small, yet significant (P<.05), increase in backfat thickness. However, carcass value, on a grade and yield basis, was not reduced by adding fat.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Fat; Calorie-protein ratio; Performance; Basal ration; Lysine